Molecular modeling and dynamic simulations of agglutinin-like family members from Candida albicans: New insights into potential targets for the treatment of candidiasis. Issue 16 (10th December 2018) - von Ranke, Natalia L.; Bello, Murilo L.; Cabral, Lucio M.; Castro, Helena C.; Rodrigues, Carlos R.
Abstract : Infections by Candida albicans in immune compromised patients cause significant morbidity and mortality. In the search for potential molecular targets for drug development, the family of agglutinin-like proteins (Als) in C. albicans have been identified due to numerous attributes associated with high virulence, most prominently due to their role in adherence. Here, molecular models of individual members of the Als family illustrated common and unique structure features. Additionally, dynamic simulations were performed to display regions of high mobility. The results showed variations between Als members in the fluctuation of the A1B1 protein loop, which is located at the entrance to the peptide binding cavity, suggesting that this feature may be a factor contributing to observed differences in affinities to ligands and adhesion properties. Molecular docking results further suggested that ligand affinity could be influenced by movements in the A1B1 loop. In addition, a new site was identified in Als in an area adjacent to the peptide binding cavity that could serve as a new binding site for the design of future anti-adhesion ligands that provide increased specificity inhibiting Als proteins from C. albicans .